2022
DOI: 10.47197/retos.v46.93720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute omega 3 supplementation reduces serum tumor necrosis factor-alpha (TNF-a) levels, pain intensity, and maintains muscle strength after high-intensity weight training

Abstract: This study aims to analyze the acute effect of omega 3 supplementation on serum TNF-α levels, pain intensity, and muscle strength after high-intensity weight training. A total of 20 adult males with a BMI of 18.00-24.99 were enrolled in this study. Subjects were divided into 2 groups, namely (K1) with placebo and (K2) with omega 3 supplementation with a dose of 1000 mg (540 mg EPA and 360 mg DHA). The intervention was carried out 24 hours after high-intensity weight training. The data in this study were taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In inflammatory situations, other myokines such as TNF-α and IL-10 are also expressed (Santoso et al, 2019;Porto et al, 2023;Volpe-Fix et al, 2023). TNF-α is one part of the pro-inflammatory cytokines that trigger muscle pain (Fernández-Lázaro et al, 2020;Ayubi et al, 2022;Nanavati et al, 2022). TNF-α produced by heart cells is responsible for the inflammatory response to stress (Santoso et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In inflammatory situations, other myokines such as TNF-α and IL-10 are also expressed (Santoso et al, 2019;Porto et al, 2023;Volpe-Fix et al, 2023). TNF-α is one part of the pro-inflammatory cytokines that trigger muscle pain (Fernández-Lázaro et al, 2020;Ayubi et al, 2022;Nanavati et al, 2022). TNF-α produced by heart cells is responsible for the inflammatory response to stress (Santoso et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is a strong foundation that physical exercise performed at high-intensity results in muscle damage and triggers an increase in pro-in ammatory cytokines such as TNF-a and IL-6 in the blood [16], [26]. On the other hand, at the right levels, TNF-a will provide protection and healing, but at excessive levels, TNF-a will cause tissue damage and trigger muscle pain [11].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that muscle pain reaches its peak 24 hours after exercise [8]- [11]. In connection with this phenomenon, currently, around 30 million people worldwide who experience DOMS are usually treated with non-steroidal anti-in ammatory drugs (NSAIDs) [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the current case, non-steroidal anti-inflammatory drug (NSAIDs) modalities are the most popular in the management of post-exercise pain [9][10][11][12]. On the other hand, the use of NSAIDs is a wrong action because it interferes with the response of muscle growth it will have an impact on hypertrophy and muscle strength [13]. In addition, the use of NSAIDs will cause dependence [14].…”
Section: Introductionmentioning
confidence: 99%